Quantifying Ship Shape in Archaeology: Evaluating 3D Geometric Morphometrics. (1st March 2020) - Dhoop, Thomas; Stark, Sarah; Olaberria, Juan‐pablo; Whitewright, Julian
Abstract: The analysis of the archaeological remains of ships and boats, in particular hull shapes, have been central to wider analysis of performance, function, and significance within past societies. This article reviews established methods of quantifying shape in ship and boat archaeology—linear measurement ratios and form coefficients—and evaluates the utility of 3D geometric morphometrics (GM). The 3D shape of 30 vessels from north‐west Europe dating between 325 BC and AD 1915 are quantified to study how hull shape relates to a vessel's function and intended operating environment. A comparison of the three methods highlights the importance of analysing the complexity of a hull in a holistic manner and demonstrates that 3D GM outperforms the traditional methods.